EFL Teachers’ Beliefs in Teaching Speaking to Elementary School Students Using Task-Based Language Teaching (TBLT) : A Case Study - Vivi Inan Lolita Sari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This research aims to explore and describe teachers' beliefs about teaching English in elementary schools. The research participants were elementary school English teachers in Kediri. The data were collected using a semi-structured interview which allowed the participants to share their thought and experiences in English teaching for young learners. By gaining insights into teachers' beliefs, this study seeks to offer a fresh perspective on effective English teaching strategies. The findings aim to empower teachers in fostering more impactful teaching environments. The teachers believed that they should consider the characteristics of young learners in teaching English and their psychological factors. Thus, teachers believed that teaching English should be fun. They used some techniques to make the teaching learning fun, for example by using pictures, videos, songs, etc.